1978
DOI: 10.1056/nejm197811092991902
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Bronchitis Associated with Graft-versus-Host Disease in Recipients of Bone-Marrow Transplants

Abstract: Graft-versus-host disease, a complication of allogeneic bone-marrow transplantation, involves primarily the skin, liver and intestines, but may also be associated with pneumonia. To determine the relation of graft-versus-host disease with pneumonia, we evaluated the autopsies of 59 allogeneic and two autologous recipients and 74 control patients with various pulmonary diseases, who had not received a bone-marrow transplant. Lymphocytic bronchitis, characterized by lymphocyte-associated necrosis of the bronchia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
4

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(86 citation statements)
references
References 11 publications
1
81
0
4
Order By: Relevance
“…1B) (8), which is in agreement with the report of Yousem (9) and that using a rat model (12). On the other hand, some have suggested that lymphocytic bronchitis is unrelated to GVHD, using canine models (13).…”
Section: Parainfluenza Virus and Adenovirus Ruling Out Infection Hsupporting
confidence: 92%
“…1B) (8), which is in agreement with the report of Yousem (9) and that using a rat model (12). On the other hand, some have suggested that lymphocytic bronchitis is unrelated to GVHD, using canine models (13).…”
Section: Parainfluenza Virus and Adenovirus Ruling Out Infection Hsupporting
confidence: 92%
“…Whereas most authors seem to agree about the important role of chronic GVHD in the pathogenesis of bronchiolitis obliterans and lymphocytic interstitial pneumonitis, [7][8][9]15,[24][25][26] the relationship between chronic GVHD and lymphocytic bronchitis remains unclear. 17,18 From a pathophysiological point of view the very low incidence of NILC in the group of patients receiving autologous stem cells provides convincing indirect evidence for the involvement of alloreactive T cells in the pathogenesis of NILC. Only one patient out of 25 (4%) autologous patients developed a NILC compared with 40 out of 272 allogeneic patients (14.7%).…”
Section: Discussionmentioning
confidence: 99%
“…7,14 In contrast, the role of chronic GVHD in the development of lymphocytic interstitial pneumonitis or bronchitis has not been settled. [15][16][17][18][19] In two recent series of 29 and 18 patients, chronic GVHD was identified as a potent risk factor for late-onset pulmonary syndromes. 13,14 The authors assume that alloreactivity may be the underlying mechanism of lung disease in these cases.…”
mentioning
confidence: 99%
“…Lung involvement by aGVHD is a highly controversial issue. Early works describing this entity [1,2] were later under discussion by other authors [3,4,5]. Animal models recently helped to understand this entity, and some authors consider donor T lymphocytes as one of the sources of lung damage after allogeneic hematopoietic transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have considered lymphocytic bronchitis to be the pulmonary manifestation of acute graft versus host disease (aGVHD) [1]. However, a pulmonary interstitial syndrome with interstitial and peribronchial lymphocytic infiltrate with very good response to steroid treatment resembling aGVHD was later described [2].…”
Section: Introductionmentioning
confidence: 99%